Membangun Generasi Bebas Narkoba di Lingkungan Anak-anak melalui Edukasi dan Pendampingan Bersama Badan Narkotika Nasional (BNN) - Maulida Maghfirotul Mudrikah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Talking about drugs is certainly not a foreign thing anymore, because a little news warning about drugs is widely spread on various social media, even in schools we have often heard. Not a few people who consume drugs excessively, ranging from adults, teenagers and even children. Therefore, MIT-18 KKN Students Posko 27 have a work program, namely the socialization of drug prevention in early childhood. It is very important to provide education about drug prevention from an early age. This work program was held because of the many complaints and concerns of the Payung village community regarding the large number of village teenagers who consume illegal drugs. In this socialization, KKN Students Posko 27 collaborated with the National Narcotics Agency (BNN) to provide education related to drugs. The method of implementing this socialization begins with; a). Submission of a proposal to the BNN (National Narcotics Agency), b). Submission of a socialization permit letter to the principal of SD N 1 Payung, c). Preparing a place for the implementation of socialization, d). Drug education materials by BNN, e). Ice Breaking, f). Drug related Quizzes and Questions.